Ways of coping and behavior in adolescent resilient spectator violence among peers - Quintana Peña, Alberto (2009)
Examines the relationship between ways of coping and resilience behavior in adolescent spectators peer violence in educational environments. Inquires whether the types of viewers recognized by the literature (indifferent, guilty, amoral and prosocial), they differ on the coping modes with stress dealing with these situations, and if, on average, differ in terms of degree of resilience that they reveal. This evaluated a representative sample of the Resilience Scale, the Ways of Coping Questionnaire and a Scale Type Spectator Peer Violence (TSPV) developed by those responsible for the study. The data indicate that significant differences exist in certain ways of coping, the resilient behavior, and between it and most of the coping modes expressed by different types of peer violence among spectators. Also, it is confirmed that the scale TSPV developed for this study is valid and reliable.